Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

We have a line (in parameter):

$ x = 2\lambda $

$ y = 1-\lambda$

Find out for which values of $\lambda$ the points of the line are inside the circle of $x^2+4x+y^2-6y+5=0$

What I did:

I rewrote the circle to the form $(x+2)^2 + (y-3)^2 = 8$.

Where my problems/questions are:

  • First of all, I have trouble with the parameter representation of a line, how can I rewrite this to for example $y=ax+b$ or $ax+by=c$?

  • And there also is a problem with how to continue. I thought if replacing the $x$ and $y$ in the circle equation by $2\lambda $ and $ y = 1-\lambda$ respectively, but I get a nonsensical answer:

$(2\lambda + 2)^2 + (1-\lambda -3)^2 = 8$

$4\lambda ^2 + 4\lambda + 4 + \lambda ^2 +4\lambda + 4 = 8$

$ 5\lambda ^2 + 8\lambda =0$

$ \lambda ^2 + 1.6\lambda = 0$

And at this juncture I just quit because of the nonsensical answer I would get if continued. What am I doing wrong? What am I doing right? How does the parameter representation of a line work and how can I rewrite it into a different form?

share|improve this question
add comment

2 Answers

up vote 1 down vote accepted

You calculation contains one mistake:

it should be $8\lambda$ instead of $4\lambda,$ as explained below:

to be inside the circle, the distance for the centre must be less than the radius.

So,$(2\lambda+2)^2+(1-\lambda -3)^2$ must be $<8$

or, $4\lambda^2+8\lambda+4+\lambda^2+4\lambda+4<8$

or $5\lambda^2+12\lambda<0$

or $(\lambda-0)\{\lambda-(-\frac{12}5)\}<0$

The product of two term $<0$, so one must $<0$ and the other $>0$

If $(\lambda-0)>0$ i.e., $\lambda>0$, then $\lambda-(-\frac{12}5)<0$ or $\lambda<-\frac{12}5$ which is impossible as $\lambda>0$.

If $(\lambda-0)<0$ i.e., $\lambda<0$,

then $\lambda-(-\frac{12}5)>0$ or $\lambda>-\frac{12}5$

So, $-\frac{12}5<\lambda<0$


Alternatively, if the equation of the circle is $x^2+y^2+2gx+2fy+c=0--->(1)$

or $\{x-(-g)\}^2+\{y-(-f)\}^2=g^2+f^2-c$

If $(h,k)$ lies inside the circle, $\{h-(-g)\}^2+\{k-(-f)\}^2<g^2+f^2-c$

or $h^2+k^2+2gh+2fk+c<0--->(2)$

Here $g=3,f=-3,c=5$ and $(h,k)$ is $(2\lambda,1-\lambda)$

We can put the values of $(h,k)$ in terms of $\lambda$ in $(2)$ to reach the same destination as in the 1st method.

share|improve this answer
    
And am I right that $(1-\lambda-3)^2 = (-\lambda-2)^2?$ –  ZafarS Nov 2 '12 at 16:48
    
@ZafarS, yes $=(\lambda+2)^2$ too. Modified the answer. –  lab bhattacharjee Nov 2 '12 at 16:50
    
However, when I try to eliminate $y$, so making it like this: $(x+2)^2 + (0,5x+2)^2=*$, I get the answers $x=0$ and $x=-4.8$, however that should be $x=-2,4$ too right? Can I use the method of elimination too? –  ZafarS Nov 2 '12 at 17:10
    
*=8, I can't edit it after 5 minutes for some reason.. –  ZafarS Nov 2 '12 at 17:16
    
@ZafarS, it's not '=', but '<' –  lab bhattacharjee Nov 2 '12 at 17:29
show 5 more comments

As for converting the parametric form to a regualar form, it goes as follows. First express either $x$ or $y$ completely in terms of the parameter. Here, for example, $y=1-\lambda$, so express $\lambda=1-y$ and replace this value of $\lambda$ in the other equation. Doing so, we get $x=2(1-y)$ or $y=\frac{-x}{2}+1$. That's all.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.